The effect of meteorological conditions on productivity and protein content in chickpea at its cultivation in the southern part of the Rostov region - S. A. Vasilchenko; G. V. Metlina; N. V. Nekhoroshova (Зерновое хозяйство России)
Chickpea is the most promising crop for dry parts of the Rostov region, as it is drought tolerant, resistant to lodging, diseases and pests. The purpose of the study is to find out the deviations of productivity and protein content in chickpea depending on meteorological conditions in the southern part of the Rostov region. The experiments were conducted in 2012-2016 at the fields of the All-Russian Research Institute of Grain Crops named after I.G. Kalinenko (laboratory of cultivation technology of row-crop), which are located in the southern soil-climatic part of the Rostov region with unstable and insufficient humidity. The soil on the fields is heavy loamy, carbonaceous black earth (chernozem). The object of the study was the chickpea variety ‘Volgogradsky 10’, approved to use in the Rostov region. The article presents the results of the correlation analysis of the effect of meteorological conditions of the southern part of the Rostov region on the duration of vegetation period of chickpea, its productivity and protein content. The correlation analysis showed a great dependence of the duration of vegetation period on the amount precipitations (r=0.92) and the sum of temperatures (r=-0.86). The meteorological conditions during the second half of vegetation period, i.e. sum of temperatures (r=0.90), amount of precipitations (r=0.87) and GTK (r=0.76), had a positive effect on protein content in chickpea kernels. The regressive analysis of the effect of precipitations and air temperature on productivity and protein content showed the change of its indexes due to climatic factors. The intervals between precipitations and sum of temperatures which increase productivity and protein content have been established. During the years of study precipitations and air temperatures influenced on productivity and protein content in kernels in different ways, as the largest yields were obtained at 200-220 mm of precipitations and 1750-19500C during the vegetation period; the largest amount of protein in chickpea kernels were received at 100-120 mm of precipitations and 2100-21500C.